Influence of electric spark on hardness of carbon steel - Vakulenko, I. O.; Proydak, S. V.; Stradomski, Z.; Diadko, V. A. (Science and Transport Progress, 2014)
Purpose. The purpose of work is an estimation of influence of an electric spark treatment on the state of mouldable superficial coverage of carbon steel. Methodology. The steel of fragment of railway wheel rim served as material for research with chemical composition 0.65% С, 0.67% Mn, 0.3% Si, 0.027% P, 0.028% S. Structural researches were conducted with the use of light microscopy and methods of quantitative metallography. The structural state of the probed steel corresponded to the state after hot plastic deformation. The analysis of hardness distribution in the micro volumes of cathode metal was carried out with the use of microhardness tester of type of PMT-3. An electric spark treatment of carbon steel surface was executed with the use of equipment type of EFI-25M. Findings. After electric spark treatment of specimen surface from carbon steel the forming of multi-layered coverage was observed. The analysis of microstructure found out the existence of high-quality distinctions in the internal structure of coverage metal, depending on the probed area. The results obtained in the process are confirmed by the well-known theses, that forming of superficial coverage according to technology of electric spark is determined by the terms of transfer and crystallization of metal. The gradient of structures on the coverage thickness largely depends on development of structural transformation processes similar to the thermal character influence. Originality. As a result of electric spark treatment on the condition of identical metal of anode and cathode, the first formed layer of coverage corresponds to the monophase state according to external signs. In the volume of coverage metal, the appearance of carbide phase particles is accompanied by the decrease of microhardness values. Practical value. Forming of multi-layered superficial coverage during electric spark treatment is accompanied by the origin of structure gradient on a thickness. The effect of the superficial work-hardening from a spark according to a level can be an alternative to majority of thermal and chemical-thermal technologies of treatment of metallic materials.